Effects of Family Policy Reforms in Norway. Results from a Joint Labor Supply and Child Care Choice Microsimulation Analysis - Tom Kornstad; Thor Olav Thoresen (Statistics Norway, Research Department, 2006)
Mothers of preschool children represent one part of the population that might be able to increase its labor supply. We discuss effects of family policy changes that encourage the labor supply of these mothers, as child care fee reductions and increased availability of center-based care. Effects of policy changes are described by employing a joint labor supply and child care choice decision model. Detailed empirical results are provided with respect to mothers' labor supply, families' child care choices, public expenditures, and distributions of income and money metric utility.
Keywords: D12; D31; J22; H23; 330; : female labor supply; child care; family policy; discrete choice; microsimulation; compensating variation